2012
DOI: 10.1021/ja302649g
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Limitations of Surface Functional Group Quantification Methods: Exploratory Study with Poly(acrylic acid)-Grafted Micro- and Nanoparticles

Abstract: The amount of grafted poly(acrylic acid) on poly(methyl methacrylate) micro- and nanoparticles was quantified by conductometry, (13)C solid-state NMR, fluorophore labeling, a supramolecular assay based on high-affinity binding of cucurbit[7]uril, and two colorimetric assays based on toluidine blue and nickel complexation by pyrocatechol violet. The methods were thoroughly validated and compared with respect to reproducibility, sensitivity, and ease of use. The results demonstrate that only a small but constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(153 citation statements)
references
References 92 publications
7
145
0
1
Order By: Relevance
“…Quantitative yields were not achieved presumably due to the distribution of the boronic acid groups between the particle's "surface" and "interior" with coupling to the latter increasingly more difficult due to the steric demands. 27 These yields are similar to the well established Cu-catalysed 35 click chemistry mediated conjugation. Recently, it was shown that the yield for surface modifications of azide-functionalised nanoparticles with alkyne modified fluorescein by Cu-catalysed click chemistry was dependent on the polymerisation process, surfactants used and accessible azide groups.…”
Section: Resultssupporting
confidence: 72%
“…Quantitative yields were not achieved presumably due to the distribution of the boronic acid groups between the particle's "surface" and "interior" with coupling to the latter increasingly more difficult due to the steric demands. 27 These yields are similar to the well established Cu-catalysed 35 click chemistry mediated conjugation. Recently, it was shown that the yield for surface modifications of azide-functionalised nanoparticles with alkyne modified fluorescein by Cu-catalysed click chemistry was dependent on the polymerisation process, surfactants used and accessible azide groups.…”
Section: Resultssupporting
confidence: 72%
“…29,30 Nanoparticles are conventionally functionalized through surface amines or carboxyls 29,31 but for QDs this surface charge promotes nonspecific interactions with biomolecules and cells. 29,32 For Pdots, these charged sites for attachment are generally linked to an amphiphilic PEG polymer 24 or a PEG–phospholipid coating.…”
Section: Resultsmentioning
confidence: 99%
“…The uptake amount of TBO in 5% (v/v) AAc with a 10 kGy irradiation dose was 20.32 ± 5.45 M/cm 2 , which was similar to that observed in a PLCL film experiment (16.83 ± 11.49 M/cm 2 ). According to the report that one TBO molecule can bind to 3.4 ± 0.2 carboxyl groups, the amount of carboxyl groups on the nanofibers that reacted with 5% (v/v) AAc at 10 kGy is approximately 11 M/cm 2 [32]. The stability of grafted AAc is shown in Fig.…”
Section: Characterization Of Nanofibers Following Chemial Processesmentioning
confidence: 94%